Tectonic Geomorphology and Volcano-Tectonic Interaction in the Eastern Boundary of the Southern Cascades (Hat Creek Graben Region), California, USA - Paguican, Engielle M. R.; Bursik, Marcus I. (Frontiers in Earth Science, 2016)
The eastern boundary of the Southern Cascades (Hat Creek Graben region), California, USA, is an extensively faulted volcanic corridor between the Cascade Range and Modoc Plateau. The east-west extending region is in the transition zone between the convergence and subduction of the Gorda Plate underneath the North American Plate; north-south shortening within the Klamath Mountain region; and transcurrent movement in the Walker Lane. We describe the geomorphological and tectonic features, their alignment and distribution, in order to understand the tectonic geomorphology and volcano-tectonic relationships. One outcome of the work is a more refined morpho-structural description that will affect future hazard assessment in the area. A database of volcanic centers and structures was created from interpretations of topographic models generated from satellite images. Volcanic centers in the region were classified by morphological type into cones, sub-cones, shields and massifs. A second classification by height separated the bigger and smaller edifices and revealed an evolutionary trend. Poisson Nearest Neighbor analysis shows that bigger volcanoes are spatially dispersed while smaller ones are clustered. Using volcano centroid locations, about 90 lineaments consisting of at least three centers within 6km of one another were found, revealing that preferential north-northwest directed pathways control the transport of magma from the source to the surface, consistent with the strikes of the major fault systems. Most of the volcano crater openings are perpendicular to the maximum horizontal stress, expected for extensional environments with dominant normal regional faults. These results imply that the extension of the Hat Creek Graben region and impingement of the Walker Lane is accommodated mostly by extensional faults and partly by the intrusions that formed the volcanoes. Early in the history of a volcano or volcano cluster, melt produced at depth in the region propagates to the surface using the easiest and most efficient pathway, mostly controlled by these pre-existing extensional faults and near-surface stress fields. Continued volcano growth is less closely dependent on the regional structures, suggesting control by the development of the volcanic edifice itself.